L*a*b* color model based road lane detection in autonomous vehicles - Kazemi, M; Baleghi, Y (Bangladesh Journal of Scientific and Industrial Research, 2017)
Autonomous vehicles, as a main part of Intelligent Transportation Systems (ITS), will have great impact on transportation in near future. They could navigate autonomously in specific areas or highways and city streets using maps, GPS, video sensors and so on. To navigate autonomously or follow a road, intelligent vehicles need to detect lanes. This paper presents a method for lane detection in image sequences of a camera on top of a robotic vehicle. The main idea is to find the road area using the L*a*b* color space in consecutive frames. Subsequently, by applying this model in road area and equalization of histogram and calculation of gradient image using Sobel operator, the parameters of the lane can be calculated using a Hough transform. The proposed method is tested under various illumination conditions and experimental results indicate the good performance of the proposed method. Bangladesh J. Sci. Ind. Res. 52(4), 273-280, 2017